Language Curriculum in America and Indonesia: A Comparative Analysis for Improvement of Indonesian Character Education Practice - Mas'ud, Bulqia (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This article explores the U.S. English Language Arts Curriculum and Indonesian Language and Literature Curriculum. A comparative analysis is drawn to investigate ideological, cultural, and political economy factors that influence the development of both curricula. In addition, the educational purposes and philosophies that support both curricula are also exposed. Specifically, the discussion of the unstated purposes of the curricula shows an interesting finding. Language and literature curriculum of both countries highlight the importance of citizenship and character education and are integrated in the teaching of the curricula. However, the US language curriculum places a premium on fostering American identity, with an emphasis on increasing learning for professional workforce and career-ready individuals, which will benefit the global economy in the future. Meanwhile, Indonesian language curriculum gives priority to moral and religious instruction. The language and literature teaching are integrated in nation’s character building. After analyzing, comparing, and contrasting both curricula, the author found that America successfully instills character education to shape the worldview and characters of its citizens extracted from their clear ideology, while Indonesia is somewhat inexplicable and vague. Therefore, this article shows room for improvement for educators and educational leaders in Indonesia to be clearer in defining which character is best exposed in the curriculum.